Experimental verification of fine particle emission reduction based on acoustic agglomeration for steel sintering flue gas. Issue 1 (February 2020) - Zhao, Yun; Liu, Chang; Zhou, Hefeng; Tian, Zhangfu; Zeng, Xinwu; Gong, Changchao
Abstract: The sintering flue gas in steel production has the characteristics of large discharge capacity, fine size, high temperature, corrosion and fluctuation of working conditions, and is the primary control object of PM2.5 emission source. Traditional dust removal technologies and equipment are difficult to achieve efficient collection of fine particles. In order to quantitatively study the effect and regularity of high intensity sound waves on fine particles, the online acoustic agglomeration test system was built by using high-power pneumatic source and wave tube with abrupt section. The high intensity standing wave field of 140 to 150 dB was generated in the wide frequency range between 50 Hz and 2 kHz by the acoustic resonance synthesis, and interference from compressed airflow was avoided by the acoustic-flow separation module. Variation of the sintered flue gas PSD was obtained under different sound intensities and frequencies. Data analysis shows that the high concentration condition can greatly reduce the operation time and energy consumption. Under the action of high intensity acoustic waves with a fundamental sound pressure level of 87.3-161.8dB and duration of 3s, the measured PM2.5 removal efficiency is 16%-92%, and the optimal frequency is near 800Hz. This paper verifies the feasibility of acoustic agglomeration (AA) in the treatment of sintering flue gas, and provides a theoretical reference and technical basis for the development of PM2.5 real-time emission control device for steel production.